PEDOT:PSS polymer functionalized carbon nanotubes integrated with graphene oxide and titanium dioxide counter electrode for dye-sensitized solar cells - A M Mahmudul Hasan; Md. Abu Bin Hasan Susan (Heliyon)
This study aims at developing platinum-free dye-sensitized solar cells (DSSCs). A novel quaternary composite comprising conductive Poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) functionalized multiwalled carbon nanotube (f-MWCNT), nitrogen-doped reduced graphene oxide (Nr-GO), and titanium dioxide (TiO2) has been presented as a cost-efficient counter electrode (CE) of DSSC. The conductivity and structural property of MWCNT have been tailored by blending it with PEDOT:PSS. A small (25 wt%) incorporation of conductive polymer reduce agglomeration and increase the solution dispersity of MWCNTs that hinders due to the van der Waals and π-π stacking interaction of the individual tube. The reduced agglomeration facilitates efficient electron transport pathways as characterized by the electrochemical impedance spectroscopy (EIS) and electron imaging techniques. Among the 3 studied quaternary composites the 2:1:1 ratio of f-MWCNT/Nr-GO/TiO2 (composite-1) shows a superior performance with a charge transfer resistance (RCT) of 7.27 Ω cm2 and a cathodic peak current density (JPC) of −17.08 mA cm−2. The cell achieves a noteworthy photoconversion efficiency (PCE) of 4.25 ± 0.32 % under standard test conditions at AM1.5G. The PCE of this quaternary composite is comparable to Pt thin film (5.53 ± 0.24 %) and 9 % higher than f-MWCNT/Nr-GO binary composite. The DSSC, constructed using this quaternary composite CE, displays extended cyclability and a prolonged chemical stability even after 500 reversible redox cycles.